ANALISIS KEKUATAN BAHASA: Tinjauan Terhadap Penggunaan Bahasa Dalam Konten Video Populer - Anisa Nurlatifa (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2025)
This study is motivated by the increasing interest in understanding language maxims, which are unwritten rules in communication that regulate a person's language behavior in certain situations. These language maxims were proposed by the philosopher Grice as principles that guide successful communication. The aim of this study is to investigate the role of language maxims in everyday communicative interactions. This study aims to identify how the application of language maxims affects message understanding in different contexts and how violations of these maxims can affect the perception and interpretation of information. The method used in this study includes qualitative analysis of various communicative situations, both in informal and formal contexts. Research was conducted through case studies and observations of interactions between individuals in various communication scenarios. Based on the results of the discussion, it was found that consistent application of language maxims can strengthen understanding and clarity of the message conveyed. However, violation of this maxim can cause uncertainty in the meaning of the message and give rise to different interpretations between the parties involved in the communication. In addition, social, cultural and environmental contexts also play a role in how language maxims are applied and interpreted. This research highlights the importance of appropriateness in applying language maxims to achieve effective communicative goals and emphasizes the need to understand context in interpreting messages conveyed in everyday communication.